Planes de desarrollo urbano: instrumentos de legitimación en la expansión urbana de Ciudad Juárez, Chihuahua - Pérez Pulido, Leticia Abigail; Romo Aguilar, María de Lourdes (El Colegio de México A.C., 2022)
Urban development in the cities of Mexico’s northern border has been marked by population flows and the arrival of industry. Ciudad Juarez is no exception; despite the number of urban development plans and programs, the problems in urban areas have increased, in particular, the urban expansion accompanied by deficiencies in equipment and infrastructure. This article analyzes the participation of urban planning in the process of expansion of that city to the southeast, with the purpose of visualizing the urban development plans as instruments for legitimizing growth.